Wozy taborowe i organizacja przemarszów wojsk polskich w drugiej połowie XV wieku - Dudziński, Rafał (Acta Universitatis Lodziensis. Folia Historica, 2001)
Impedimenta carts which accompanied the troops were provided by cities and knighthood, and went to battle as part of the then levy en mass. It is, however, worth noticing that the analysis of the sources shows that not every knight’s colour party was followed by a cart. Those who possessed those means of transport used it for transporting food supplies. The food was to last 6 weeks. At the end of the XVth century, there were approximate 200 royal cities which were obliged to provide empty or furnished carts. The above-mentioned cities either levied the vehicles themselves or shared the cost of their hiring, supplying and despatching. The carts were usually accompanied by an armed escort, which is mentioned in the war statutes of 1477. The carts could be either two- or four-wheeled, and were capable of holding a load from 600 up to 650 kg. The above-mentioned impedimenta carts were also used in battle to establish fortified camps, which could become the core of army defence. Examples of such employment of the carts are well known, for instance, they are attested for the Thirteen-Years-War. In order to avoid robberies committed by the troops moving across the country, royal edicts set the organisation of army marches and prices at which the soldiers were allowed to purchase food from local people. Troops that made their way across the enemy’s area would use guides who were familiar with the region, able to show safe camp sites and help overcome natural obstacles. The knights used to live in tents while camping. The infantry and servants stayed in shelters and huts, which were surrounded by a fortified wall of earth and wood. The noblemen inside the camp would often lodge charges of theft and assault against one another. They would also start fights, which had a negative impact upon the discipline in the army.